The Role Of Creative Economy In Improving The Welfare Of Local Communities: Case Study In Tourism Area - Mahmuddin Mahmuddin; Nurul Fadhilah; Puteri Aprilani; Muhammad Hirsan Hanafi (Oikonomia : Journal of Management Economics and Accounting, 2024)
Tourism areas have great potential in improving the regional economy, especially when integrated with the creative economy sector. The creative economy, which relies on ideas, creativity and innovation, plays an important role in tourism development, not only to increase tourist attraction but also to create sustainable economic opportunities for local communities. This research aims to explore the role of the creative economy sector in improving community welfare in tourism areas, with a focus on local creative products such as handicrafts, performing arts, culinary, and design. The creative economy can reduce dependence on the seasonal tourism sector and enrich the tourist experience, while creating business opportunities and improving the skills of local communities. This research uses a descriptive qualitative approach in Indonesian tourism regions, such as Bali, Yogyakarta, and Labuan Bajo, which have great potential in this sector. Through interviews, focus group discussions, and observations, the research identified key challenges such as limited capital, market access, and adequate infrastructure. The findings of this study are expected to provide recommendations for the development of policies that support the creative economy sector, in order to create an inclusive and sustainable economy for local communities, and improve the competitiveness of tourism areas